Vaginal Myomectomy for Semipedunculated Cervical Myoma during Pregnancy - Obara, Mikitaka; Hatakeyama, Yuko; Shimizu, Yasushi (American Journal of Perinatology Reports, 2014)
Objective Cases of prolapsed myoma in which pregnancy was carried to full term or near term after vaginal myomectomy are very rare. Previously, only two such cases have been reported. In addition, both those patients had a pedunculated leiomyoma, which could be treated by twisting or clamping. Here, we report a case of a patient who was able to carry her pregnancy to term despite vaginal myomectomy for semipedunculated myoma at 13 weeks of pregnancy.Study Design This study is a case presentation.Results The myoma nucleus was removed by making an incision on the surface of the mass. Systemic and transvaginal antibiotics were prescribed after the surgery. Uterine contractions, short cervix, or cervical funneling was not observed in the remaining duration of pregnancy.Conclusion While performing myomectomy during pregnancy, removal of the myoma nucleus is safer than twisting. In addition, postoperative administration of local or systemic antibiotic agents does not adversely affect pregnancy.
Keywords: prolapsed myoma; semipedunculated leiomyoma; vaginal myomectomy; pregnancy